2018
DOI: 10.3390/s18020366
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Data Acquisition System for Automobile Dynamics Applications

Abstract: This project addresses the need for the implementation of low-cost acquisition technology in the field of vehicle engineering: the design, development, manufacture, and verification of a low-cost Arduino-based data acquisition platform to be used in <80 Hz data acquisition in vehicle dynamics, using low-cost accelerometers. In addition to this, a comparative study is carried out of professional vibration acquisition technologies and low-cost systems, obtaining optimum results for low- and medium-frequency oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…Given this situation, we recently introduced an alternative low-cost acquisition system based on the Arduino platform [1]. In that study, we validated the low-cost system presented with a professional data acquisition system for vehicular dynamics applications.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given this situation, we recently introduced an alternative low-cost acquisition system based on the Arduino platform [1]. In that study, we validated the low-cost system presented with a professional data acquisition system for vehicular dynamics applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific applications in which Arduino-or Raspberry Pi-based systems have been used for vehicular dynamics applications are still limited. In the system presented in a previous article [1], we already have shown that it was possible to dynamically use a system based on an Arduino microcontroller to perform dynamic measurements in vehicles. However, little attention has been given in the relevant literature to improving the sampling frequency and the reliability of these low-cost systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Gonzales et al (2018), the use of low-cost devices for obstacle avoidance in automotive engineering was reported. The authors in particular used an Arduino Microcontroller to acquire data to be used in vehicle dynamic analysis, demonstrating that such a low-cost technology is applicable to the automotive industry, reducing project costs [16][17][18]. Negrete et al (2018) reported how the automation of small-and large-scale agriculture is of colossal importance, because applying mechatronic technologies to agriculture would help to stimulate productivity in the Mexican agricultural industry [19].…”
Section: Introductionmentioning
confidence: 99%